PREDICTION OF ANTIFUNGAL ACTIVITY, DRUG-LIKENESS, AND TOXICITY OF Curcuma xanthorrhiza COMPOUNDS USING PASS Online, SwissADME, and PKCSM: PREDIKSI AKTIVITAS ANTIJAMUR, SIFAT SEPERTI OBAT (Drug-Likeness), DAN TOKSISITAS SENYAWA Curcuma xanthorrhiza MENGGUNAKAN PASS Online, SwissADME, DAN pKCSM - Nimas Ezrawati; Julian Parego; Aulya Ceta Pranata; Ahmad Marra Al Haqqi; Jheptianto Pernando; Dodi Iskandar (PT. ROCE WISDOM ACEH, 2026)
This study aimed to analyze the antifungal potential of bioactive compounds in Java turmeric (Curcuma xanthorrhiza) against pathogenic fungi in oil palm plants using an in silico approach through PASS Online, SwissADME, and PKCSM. PASS Online analysis showed that the oxygenated sesquiterpene group exhibited the highest antifungal activity compared to monoterpenes and basic curcuminoids. Compounds such as Bisacurone, Bisacurone A, Bisacurone B, and Bisacurone C demonstrated the highest probability activity value of 0.767, while Bisacurone epoxide showed a value of 0.729. These compounds are predicted to act through mechanisms involving plasma membrane disruption, inhibition of ergosterol biosynthesis, and increased oxidative stress in fungal cells. SwissADME analysis indicated that most compounds exhibited physicochemical properties conducive to biological activity, including good solubility, balanced lipophilicity, stable bioavailability scores, and compliance with the Lipinski, Veber, Egan, and Muegge drug-likeness parameters. The bisacurone and epoxide sesquiterpene groups demonstrated the most optimal combination of membrane permeability, structural flexibility, and biological interaction capability. Physicochemical property analysis also revealed that compounds with moderate molecular weight, balanced TPSA values, and optimal numbers of hydrogen-bond donors and acceptors exhibited greater antifungal potential. Meanwhile, PKCSM analysis showed that the majority of compounds were neither mutagenic nor hepatotoxic. Monoterpene compounds and the bisacurone group demonstrated relatively safe environmental toxicity profiles, indicating their potential for development as environmentally friendly biofungicides. However, Bisacurone epoxide showed potential AMES toxicity, indicating the need for further in vitro and in vivo testing. Overall, the study results indicate that Curcuma xanthorrhiza has significant potential as a source of natural antifungal compounds for sustainable control of fungal diseases in oil palm plants with improved environmental safety.